IMPLEMENTASI PENGEMBANGAN KURIKULUM 2013 PADA PEMBELAJARAN PAI - Amaliyah Amaliyah (QATHRUNÂ, 2020)
The purpose of this study was to determine the implementation of learning at SMAS Al Ma'arif and SMKN 3 Cilegon, curriculum development in 2013 as well as opportunities, obstacles and challenges for implementing 2013 Curriculum Development in the implementation of Islamic Education learning at SMAS Al Ma'arif and SMKN 3 Cilegon. This research uses descriptive qualitative research. The results showed SMA Al Ma'arif and SMK Negeri 3 Cilegon 1) Implementation of Islamic Education in SMAS Al Ma'arif and SMKN 3 Cilegon, In general, they have implemented learning based on the 2013 curriculum although it is not yet perfect, this is evidenced by the cultivation of religious values. and development of character education through school literacy activities carried out at the beginning and end of learning and using IT-based learning methods; 2) The development of the 2013 curriculum at SMAS Al Ma'arif and SMK Negeri 3 Cilegon has been well developed, although there are slight differences at Al Ma'arif High School, the excellence is through mulok lessons and cross-interest subjects while at SMKN 3 Cilegon the demands of the world of work and science and technology as well as local content in both Intracurricular and Extracurricular activities; 3) Implementation of 2013 Curriculum Development in the implementation of Islamic Education learning at SMAS Al Ma'arif and SMKN 3 Cilegon in general has been going well although it is not yet perfect with the differences at Al Ma'arif High School, limited facilities and PAI learning media affect skills assessment, but work The same and exemplary all teacher councils provide positive values ​​to students, while at SMKN 3 Cilegon students lack interest in reading the Qur'an and the formation of learning groups for learning to read and write the Qur'an requires the cooperation of parents, teachers and school committees.